Association Between Social Support and Medication Literacy in Chinese Patients With Coronary Heart Disease - Li Qiao (Frontiers Media S.A., 2021)
Background: The level of medication literacy is very important to control symptoms and improve the prognosis of patients with coronary heart disease (CHD). The positive role of social support is able to promote patient health outcomes. However, few studies have addressed the association between social support and medication literacy in patients with CHD. The purpose of this study is to investigate the status of medication literacy and social support, and confirm the association between them in patients with CHD.Methods: This cross-sectional study investigated 416 participants, and was conducted in a grade a hospital in China. Three different survey instruments were applied: The Demographic Characteristics Questionnaire, the Chinese Version of the Medication Literacy Scale, and the Social Support Rating Scale. Pearson correlation analysis and ordinal logistic regression analysis were performed to analyze data.Results: The results showed that the mean score of medication literacy among the 416 participants was 4.96 ± 4.68, 48.8% (203) participants with inadequate medication literacy. The independent determinants of medication literacy include gender, education level, course of disease, number of medicines, and subjective support in social support. The mean score of social support was 41.05 ± 6.16. The Pearson correlation analysis indicated that social support was positively correlated with medication literacy (r = 0.398, P < 0.01).Conclusion: The study shows that the level of medication literacy and social support for patients with CHD are inadequate. Social support levels could have a positive effect on medication literacy of patients.